IMPLEMENTASI SISTEM PENGAMBILAN KEPUTUSAN PEMILIHAN JURUSAN DI SMKN 1 BANDAR LAMPUNG MENGGUNAKAN METODE AHP DAN TOPSIS - Nugroho, Handoyo Widi; Susanti, Yus (INTEGER: Journal of Information Technology, 2024)
SMK Negeri 1 Bandar Lampung is a vocational school. Students often choose the wrong major because it does not suit their abilities, this is because they do not know the differences between several majors and there is no more detailed information about majors. With a combination of the AHP and TOPSIS methods, a decision-making system has been implemented in determining majors at SMKN1 Bandar Lampung from several predetermined criteria, namely Report Card Scores, Academic or Non-Academic Achievement Scores and Talent Interest Scores, job opportunities. AHP is used to determine the weight of each criterion. From this research it is known that the highest weight of the criteria resulting from processing with AHP is a Talent Interest Value of 47%. Meanwhile, ranking with TOPSIS resulted in Accounting (AK) being the alternative that had the best alternative value compared to the other alternatives so that it was chosen as the leading major at SMKN1 Bandar Lampung.